2019
DOI: 10.1007/s11136-019-02269-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tardive dyskinesia on quality of life in patients with bipolar disorder, major depressive disorder, and schizophrenia

Abstract: PurposeTardive dyskinesia (TD) is a common but serious hyperkinetic movement disorder and side effect of antipsychotic medications used to treat bipolar disorder (BD), major depressive disorder (MDD), and schizophrenia (SZ). The purpose of this study was to evaluate health-related quality of life (HRQoL) in a population with diagnoses for BD, MDD, or SZ by comparing patients with TD (n = 197) with those without TD (n = 219). HRQoL in each group was also compared with HRQoL of the general population.MethodsThis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
(20 reference statements)
0
33
0
Order By: Relevance
“…Social withdrawal and social isolation are increased in patients with schizophrenia or mood disorders who have antipsychotic-induced TD. 29 , 32 These types of negative social effects of TD are experienced by both patients and caregivers. For example, social isolation has been reported by 72.7% of the patients with TD and 18.2% of the caregivers, making it among the most commonly reported negative impacts of TD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social withdrawal and social isolation are increased in patients with schizophrenia or mood disorders who have antipsychotic-induced TD. 29 , 32 These types of negative social effects of TD are experienced by both patients and caregivers. For example, social isolation has been reported by 72.7% of the patients with TD and 18.2% of the caregivers, making it among the most commonly reported negative impacts of TD.…”
Section: Resultsmentioning
confidence: 99%
“… 10 As a result, many patients with TD report feeling embarrassed by their medical condition (eg, feeling like people are staring at them in public places). 10 , 29 , 31 , 39 Many patients and caregivers describe emotional and social impacts of TD as the most debilitating features of this disease. 29 For example, in a series of qualitative interviews, Farber and colleagues 16 found that unwanted attention related to TD was the most common negative effect of disease, reported by 90.9% of the patients and 45.5% of the caregivers In another study, 75.5% of the patients with TD reported feelings of self-consciousness or embarrassment related to their involuntary movements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reputed anosognosia of patients about TD and its lack of impact on quality of life have been called into question. In an online survey of a selected sample of patients with various psychiatric diagnoses, 2 TD subjects had worse figures for health-related quality-of-life scores and social withdrawal than those without TD, and this was particularly true of those with schizophrenia, a surprising finding given that approximately 50% of subjects with schizophrenia have apparently no or low awareness of TD. 3 In a cohort of 204 patients living with a schizophrenia spectrum disorder (54%) or another psychiatric condition and TD, over 40% reported that their involuntary movements had at least some impact on their quality of life, and three-quarters felt self-conscious or embarrassed about these movements.…”
Section: Epidemiology and Functional Impairmentmentioning
confidence: 96%
“…2 In addition to the physical symptoms experienced by patients, TD can also have a prominent effect on emotional and mental well-being. 3 This is evident in a 2019 study that reported patients with TD typically have a significantly lower quality of life. The effect of TD on a patient's quality of life was further emphasized by data correlating more severe TD symptoms with a lower clinician and self-reported quality of life.…”
Section: Introductionmentioning
confidence: 98%